Chlorogenic acid inhibits trimethylamine-N-oxide formation and remodels intestinal microbiota to alleviate liver dysfunction in high l-carnitine feeding mice. Issue 21 (24th September 2021) - Zhang, Xiangnan; Shi, Lin; Chen, Rui; Zhao, Yan; Ren, Daoyuan; Yang, Xingbin
Abstract : Chlorogenic acid alleviates liver dysfunction in l -carnitine feeding mice via inhibiting trimethylamine- N -oxide (TMAO) formation and reconstructing the intestinal microbiota. Abstract : High l -carnitine ingestion has been shown to cause liver injury, mechanically due to an elevated circulating level of trimethylamine- N -oxide (TMAO), a gut microbiota-derived metabolite from l -carnitine. This study aimed to investigate whether chlorogenic acid (CGA), a health-promoting polyphenol, could inhibit TMAO formation and thereafter might prevent l -carnitine-induced liver injury in mice. Feeding of mice with 3% l -carnitine in drinking water increased the serum and urinary levels of TMAO ( p < 0.01 vs. Normal), whereas the serum and urinary TMAO formation was sharply reduced by CGA administration ( p < 0.01). At the phylum level, CGA inhibited the l -carnitine-induced increase in the abundance of Firmicutes and Proteobacteria, while it promoted Bacteroidetes . At the genus level, CGA notably increased the abundance of Akkermansia and Bacteroides, but reduced the population of Erysipelatoclostridium, Faecalibaculum and Erysipelotrichaceae in high l -carnitine feeding mice. Meanwhile, CGA caused strong inhibition against the increase of liver injury markers ( i.e. AST, ALT and ALP), hepatic inflammatory cytokines ( i.e. IL-1, IL-6, TNF-α and TNF-β) and dyslipidemia ( i.e. TC, TG, LDL-C and HDL-C) in l -carnitine-fed mice ( p < 0.05). These findings suggest that CGA holds great potential to alleviate liver dysfunction induced by high l -carnitine ingestion. The beneficial effect might be attributed to the protection against TMAO formation and the improvement of the health-promoting gut microbiota, as well as the antioxidant and anti-inflammatory properties of CGA.